The Use of Virtual Reality in Craving Assessment and Cue-Exposure Therapy in Substance Use Disorders - Hone-Blanchet, Antoine; Wensing, Tobias; Fecteau, Shirley (Frontiers in Human Neuroscience, 2014)
Craving is recognized as an important diagnosis criterion for substance use disorders (SUDs) and a predictive factor of relapse. Various methods to study craving exist, however, suppressing craving to successfully promote abstinence remains an unmet clinical need in SUDs. One reason is that social and environmental contexts recalling drug and alcohol consumption in the everyday life of patients suffering from SUDs often initiate craving and provoke relapse. Current behavioural therapies for SUDs use the cue-exposure approach to suppress salience of social and environmental contexts that may induce craving. They facilitate learning and cognitive reinforcement of new behavior and entrain craving suppression in the presence of cues related to drug and alcohol consumption. Unfortunately, craving often overweighs behavioural training especially in real social and environmental contexts with peer-pressure encouraging the use of substance, such as parties and bars. In this perspective, virtual reality is gaining interest in the development of cue-reactivity paradigms and practice new skills in treatment. Virtual reality enhances ecological validity of traditional craving induction measurement. In this review, we discuss results from 1) studies using virtual reality and alternative virtual agents in the induction of craving and 2) studies combining cue-exposure therapy with virtual reality in the promotion of abstinence from drugs and alcohol use. They used virtual environments, displaying alcohol and drugs to SUD patients. Moreover, some environments included avatars. Hence, some studies have focused on the social interactions that are associated with drug seeking behaviours and peer pressure. Findings indicate that virtual reality can successfully increase craving. Studies combining cue exposure-therapy with virtual environment however reported mitigated success so far.